Reviews - Philip Barker; Gillian Jordan; Janet Hanson; Roger Hartley (Association for Learning Technology, 2001)
This is another in the long list of '500 Tips' series, published by Kogan Page. Phil Race, the author, is a well-known name in learning and teaching and has published extensively. The presentation of advice in this way is clearly a well-tested formula and, judging by the copies from the series in my own institution's library, these are frequently borrowed books, but I wonder whether this format is now a little overused? Advice from a guru can be very valuable, but in an era of evidence-based practice it is even better if the advice is backed up with references to facilitate the reader's further research in the area. Unfortunately in this book references are few and far between. There is a short list of suggested further reading but, for example, in the section on being a group member, where the work of Belbin is referred to, this is not referenced and Belbin does not appear in the subsequent reading list.